2008
DOI: 10.1111/j.1365-2621.2006.01232.x
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of policosanols from hydrolysed rice bran wax by high‐intensity ultrasound

Abstract: This study provided a detailed method for extraction and purification of policosanols from hydrolysed rice bran wax (RBW) by high-intensity ultrasound (HIU), where the hydrolysis of RBW under HIU was focused. The optimised operating conditions for hydrolysis were as the following: 20 kHz, 100 W, 1:2 of wax to 4% sodium hydroxide (w:v) and 50 min at ambient temperature, under which the hydrolysis rate of 94.3% was obtained. Thereafter, policosanols were extracted and purified from the hydrolysed RBW. With the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…During both processes, a considerable amount of by-product is produced, some of which contains more or less quantities of potential ingredients for functional food, nutraceuticals and pharmaceutical manufacture [ 9 ]. These ingredients include mainly of γ-oryzanol, tocotrienol, tocopherol, phytosterol, lecithin, carotenoids and long-chain alcohols [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…During both processes, a considerable amount of by-product is produced, some of which contains more or less quantities of potential ingredients for functional food, nutraceuticals and pharmaceutical manufacture [ 9 ]. These ingredients include mainly of γ-oryzanol, tocotrienol, tocopherol, phytosterol, lecithin, carotenoids and long-chain alcohols [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…39 In the present study, following the method of Cravotto et al 39 with some modification, a higher yield of policosanol was obtained (Table 1). Liu et al 47 reported that ultrasonic power is more important in the hydrolysis of RBW than ultrasonic frequency. This explains why good policosanol yield was achievable in this study even though low ultrasound frequency was used (50 Hz).…”
mentioning
confidence: 99%
“…www.nature.com/scientificreports/ the extracted PCs changed through a multistep process. Liu et al 37 reported that crude PC extracted from RBW appeared dark brown, but after the purification step, the color of the obtained PCs changed to white powder. A comparison of γ-oryzanol, phytosterol and PC contents of extracts from transesterified FC and RBW using the SUBFDME and SE methods is shown in Table 4.…”
Section: Resultsmentioning
confidence: 99%